Identification of a new cell-penetrating peptide derived from the african swine fever virus CD2v protein. (1st January 2021) - Yang, Shunli; Zhang, Xinming; Cao, Yuying; Li, Shuo; Shao, Junjun; Sun, Shiqi; Guo, Huichen; Yin, Shuanghui
Abstract: The African swine fever virus (ASFV) is a huge and complex DNA virus that can lead to the acute death of pigs and cause huge losses to the global swine industry. The CD2v protein is a transmembrane protein encoded by the ASFV's EP402R gene, which can effectively inhibit the bystander lymphocyte proliferation in response to mitogens and mediate the absorption of red blood cells to ASFV-infected cells. The CD2v protein contains repetitive amino acid sequences ([KPCPPP]3 labeled as RAAS), which is reported as a genetic marker and an epitope. However, the specific biological function of the RAAS is unknown. Here, we have found that the truncated CD2v protein with RAAS can enter Chinese hamster ovary cells, but the truncated CD2v protein without RAAS cannot enter the cells. Also, the RAAS can carry the macromolecular protein EGFP to enter various cells through multiple endocytic processes that are dependent on time, concentration, and location. Besides, the RAAS enter the cells via the macropinocytosis or the clathrin-mediated endocytosis. These results indicate that the RAAS can function as a cell-penetrating peptide that provides a new insight for ASFV research and has potential application value as a tool for drug delivery.